Detection and 3D visualization of Brain tumor using deep learning and polynomial interpolation - Tuhin, Md. Akram Hossan; Pramanick, Tarunya; Emon, Humayoun Kabir; Rahman, Wasiur (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.